Correction: Individual and temporal variability of the retina after chronic bilateral common carotid artery occlusion (BCCAO). - Sergio Crespo-Garcia; Nadine Reichhart; Sergej Skosyrski; Marco Foddis; Jim Wu; Aleksandar Figura; Christina Herrspiegel; Martina Füchtemeier; Celeste Sassi; Ulrich Dirnagl; Antonia M Joussen; Olaf Strauss (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0193961.].